Siple Dome Highlights: Stable isotopes - Steig, Eric J.; White, James (IEDA: US Antarctic Program Data Center, 2003)
This data set is part of the WAISCORES project, an NSF-funded project to understand the influence of the West Antarctic ice sheet on climate and sea level change. WAISCORES researchers acquired and analyzed ice cores from the Siple Dome, in the Siple Coast region, West Antarctica. This data set provides measurements of stable isotopes of water and deuterium excess for the Siple Dome ice cores. The shallow cores from Siple Dome were analyzed for isotopes with sub-annual temporal detail.